2022
DOI: 10.3390/antibiotics11030305
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of MCR-1 Producing Enterobacterales Isolated in Poultry Farms in the United Arab Emirates

Abstract: Data on the prevalence of MCR-producing Enterobacterales of animal origin are scarce from the Arabian Peninsula. We investigated the presence and variety of such strains from fecal specimens of poultry collected in four farms in the United Arab Emirates. Colonies from ten composite samples per farm grown on colistin-supplemented plates were PCR-screened for alleles of the mcr gene. Thirty-nine isolates selected based on species, colony morphology, and plasmid profile were subjected to whole genome sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…It should be noted that during the study period (i.e., 2009–2015), in the absence of clear technical guidelines, several laboratories either used the unreliable disk diffusion or automated susceptibility testing methods or did not test for colistin susceptibility, likely contributing to the excessive use of this drug. Although the presence of transferable colistin resistance genes was not studied in the current project, previous observations suggest that, while common among animal isolates [ 25 ], plasmid-mediated colistin resistance is either absent or relatively rare among clinical isolates in the region [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that during the study period (i.e., 2009–2015), in the absence of clear technical guidelines, several laboratories either used the unreliable disk diffusion or automated susceptibility testing methods or did not test for colistin susceptibility, likely contributing to the excessive use of this drug. Although the presence of transferable colistin resistance genes was not studied in the current project, previous observations suggest that, while common among animal isolates [ 25 ], plasmid-mediated colistin resistance is either absent or relatively rare among clinical isolates in the region [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sonnevend et al investigating MCR-producing Enterobacterales of animal origin from fecal samples of poultry collected in four farms in the United Arab Emirates. The study revealed that mcr-1 positive strains were identified in 36 of the 40 samples Current Situation of Escherichia coli Antibiotic Resistance in Food-producing Animals, Wild… DOI: http://dx.doi.org/10.5772/intechopen.108896 (90%) [49]. Thirty-four multi-drug resistant E. coli of 16 different sequence types, two Escherichia albertii, two Klebsiella pneumoniae, and one Salmonella minnesota were identified [49].…”
Section: Current Situation Of E Coli Antibiotic Resistance In Food-pr...mentioning
confidence: 99%
“…The study revealed that mcr-1 positive strains were identified in 36 of the 40 samples Current Situation of Escherichia coli Antibiotic Resistance in Food-producing Animals, Wild… DOI: http://dx.doi.org/10.5772/intechopen.108896 (90%) [49]. Thirty-four multi-drug resistant E. coli of 16 different sequence types, two Escherichia albertii, two Klebsiella pneumoniae, and one Salmonella minnesota were identified [49]. Beyond various aminoglycoside, tetracycline, and cotrimoxazole resistance genes, seven of them also carried ESBL genes and one blaCMY-2.…”
Section: Current Situation Of E Coli Antibiotic Resistance In Food-pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia albertii also has been detected in poultry faeces/GI tract contents and meat (e.g. (8,(23)(24)(25) and in domestic mammals (e.g. pig, cat) and both terrestrial and marine wild mammal species (e.g.…”
Section: Introductionmentioning
confidence: 99%